Contribution to the Adaptation of the Submerged Dike of Avlékété to Climate Change in the Republic of Benin - Hountondji, Babilas; Ayitchéhou, Lambert Kpadédji; Codo, François de Paule; Aina, Martin Pépin (Sustainable Marine Structures, 2026)
This article presents the results of various 1D simulations performed on the existing breakwater in Avlékéte, a critical erosion site for economic stability, environmental preservation, community resilience, and sustainable development, with a view to implementing innovative coastal protection measures to safeguard the coast for future generations in the Republic of Benin. To define the morphology along the coastline, different design simulations are carried out. A first design simulation was carried out, including a breakwater but without a lagoon, then a second without a breakwater as a hard element but with a lagoon, then a third smooth including a breakwater but without a lagoon and finally a fourth smooth including a breakwater and with a reduced wave height at the breakwater but without a lagoon which is the most appropriate approach. In order to study the morphological stability of the transverse profile of the breakwater, a one-dimensional XBeach simulation, Surfbeat mode, was carried out with the most difficult wave conditions while considering a breakwater as a non-erodible layer. The results from these simulations confirm those of the studies commissioned by the Ministry of Living Environment and Transport in charge of Sustainable Development (MCVT) in February 2023. The study of the morphological stability of the transverse profile of the breakwater led to a revised model, which shows a limited restructuring of the beach, a propagation towards the shore, and therefore an erosion of the breakwater. The profile retained at the end of the study is an equilibrium profile. ER